Myocardial Deformation in Cardiac Amyloid Light-chain Amyloidosis: Assessed with 3T Cardiovascular Magnetic Resonance Feature Tracking - Rui Li (Nature Portfolio, 2017)
Abstract Clinically, assessment of myocardial function is essential in patients with amyloid light-chain cardiac amyloidosis (AL-CA) to predict outcome and determine therapeutic approach. The aim of this study was to investigate the feasibility of cardiovascular magnetic resonance (CMR)-derived feature tracking algorithm for assessing left ventricular (LV) myocardial deformation in AL-CA, and to determine if these abnormal myocardial deformation parameters are correlated to impaired LV myocardial microvascular dysfunction. A total of 42 AL-CA patients, including 26 with preserved systolic function and 16 with impaired LVEF, and 35 healthy controls were enrolled and underwent CMR examination. Our result indicated that AL-CA patients had significantly reduced global peak strain (PS) (longitudinal, circumferential, and radial) (all P < 0.05). AL-CA patients with normal LVEF showed preserved longitudinal PS at apical and significantly reduced longitudinal PS at mid and basal segments. By Spearman’s rank correlation analysis, the LV regional radial, circumferential, and longitudinal myocardial deformation values were correlated to myocardial upslope and MaxSI in CA, regardless of LVEF. This study indicated that the abnormal LV myocardial deformation of AL-CA patients can be monitored using feature tracking CMR, even in those with preserved LVEF; and the myocardial deformation was associated with coronary microvascular dysfunction.